2021
DOI: 10.7554/elife.64090
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell chromatin accessibility profiling of glioblastoma identifies an invasive cancer stem cell population associated with lower survival

Abstract: Chromatin accessibility discriminates stem from mature cell populations, enabling the identification of primitive stem-like cells in primary tumors, such as glioblastoma (GBM) where self-renewing cells driving cancer progression and recurrence are prime targets for therapeutic intervention. We show, using single-cell chromatin accessibility, that primary human GBMs harbor a heterogeneous self-renewing population whose diversity is captured in patient-derived glioblastoma stem cells (GSCs). In-depth characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 61 publications
1
51
0
Order By: Relevance
“…Programs 1 and 2 had some notable differences from all previously described subtypes. Program 1 was similar to both AC and MES, which agrees with the recently reported stratification of the MES subtype and heterogeneity of the AC subtype in GBM 72 . It was strongly enriched for genes associated with cell respiration, and was negatively associated with endothelial cells.…”
Section: Resultssupporting
confidence: 90%
“…Programs 1 and 2 had some notable differences from all previously described subtypes. Program 1 was similar to both AC and MES, which agrees with the recently reported stratification of the MES subtype and heterogeneity of the AC subtype in GBM 72 . It was strongly enriched for genes associated with cell respiration, and was negatively associated with endothelial cells.…”
Section: Resultssupporting
confidence: 90%
“…These sites include motifs for factors that affect invasion (FOXD1 and ALDH1A3), response to immune signalling (SP1) and neural commitment (OLIG2, AHR). Combined with scRNA-seq, these findings confirm the heterogeneity even within the tumour-initiating CSCs and highlight the potential challenges in targeted therapies [ 66 , 67 ].…”
Section: The Epigenetic Foundation Of Tumour Plasticitymentioning
confidence: 64%
“…The profound shift in co-accessibility of DNA elements observed with KMT5B/C loss demonstrates the complexity of cis-regulation in these tumours. Heterogenous chromatin landscapes have recently been shown to play an important role in glioma stem-like cell diversity in adult glioblastoma (Guilhamon et al, 2021), whilst in H3G34R/V mutant glioma, it was recently shown that the specific lineage context of these tumours may facilitate PDGFRA co-option through a chromatin loop connecting PDGFRA to GSX2 regulatory elements, promoting PDGFRA overexpression (Chen et al, 2020). A fundamental consequence of the altered gene expression landscape observed with KMT5B loss is a significant increase in the transcriptional heterogeneity, in patient samples as well as model systems, as has also been observed with the histone demethylase KDM5B in breast cancer (Hinohara et al, 2018).…”
Section: Discussionmentioning
confidence: 99%